pengembangan Transforming Explanatory Text Understanding Through Interactive 3D Flash Cards - Khafidz, Ahmad Nur; Mulyani, Petra Kristi (Jurnal Pendidikan Indonesia, 2025)
Reading comprehension skills are crucial in Indonesian language learning, particularly for understanding explanatory texts that require logical analysis of cause-and-effect relationships. However, low student engagement and limited access to interactive learning media often hinder learning outcomes. This study aims to develop interactive 3D flashcard media using the Assemblr Edu application with Augmented Reality (AR) features. This media aims to improve student understanding through an immersive, constructivist-based learning experience. The study employed a quantitative method with a Research and Development (R&D) approach, following the ADDIE model. Data was collected through observation, interviews, needs surveys, expert validation, documentation, and learning outcome tests. Data analysis included normality tests and t-tests to compare the control and experimental groups. The results showed that AR-based media significantly improved students' reading skills. These findings suggest that AR can enhance motivation, engagement, and learning effectiveness. This study contributes to developing innovative technology-based learning media for language education. The implications of this study indicate that innovative learning media can significantly improve students' understanding of the structure and content of explanatory texts. These results indicate that teachers must consider integrating visual and interactive technology in language learning, especially in informative and complex materials.